Multisensory contributions to skin‐cosmetic product interactions - Spence, Charles; Zhang, Tianyi (International journal of cosmetic science, 2024)
The human face is one of the most salient regions of the body surface. Ratings of facial attractiveness, as well as judgements of a person's age, are influenced by the appearance of facial skin (not to mention the presence/absence of wrinkles). Unsurprisingly, many consumers spend huge amounts of money on trying to protect, maintain, and/or enhance their facial appearance. As highlighted by the evidence presented in this narrative review, both the skin and the cosmetic products that many consumers use are fundamentally multisensory in nature. The complex interaction between the particular skin site stimulated and the multisensory attributes of the product (e.g., when it is applied) can exert a number of effects on an individual's mood, their emotions, as well as on their self‐perception (and self‐confidence), over‐and‐above any functional effects that the cream or lotion may have on the skin itself. In this narrative historical review, the literature on the multisensory perception of facial skin is summarized and critically evaluated. Multisensory interactions taking place between the cosmetic product, its packaging, as well as its use/application at the sensory, cognitive, and emotional levels are all discussed. Le visage humain est l'une des régions les plus visibles de la surface du corps. L'apparence de la peau du visage (sans parler de la présence ou de l'absence de rides) influe sur l'évaluation de l'attrait du visage et sur le jugement de l'âge d'une personne. Il n'est donc pas surprenant que de nombreux consommateurs dépensent des sommes considérables pour essayer de protéger, d'entretenir et/ou d'améliorer l'apparence de leur visage. Comme le montrent les données présentées dans cette synthèse, la peau et les produits cosmétiques utilisés par de nombreux consommateurs sont fondamentalement multisensoriels par nature. L'interaction complexe entre le site cutané stimulé et les attributs multisensoriels du produit (par exemple, lorsqu'il est appliqué) peut exercer un certain nombre d'effets sur l'humeur et les émotions d'un individu, ainsi que sur la perception de soi (et la confiance en soi), au‐delà de tout effet fonctionnel que la crème ou la lotion peut avoir sur la peau elle‐même.